Asymmetric Effects of the Financial Crisis : Collateral-Based Investment-Cash Flow Sensitivity Analysis - Khramov, Vadim (IMF Working Papers; Working Paper ;, 2012)
This paper uses the financial crisis of 2008 as a natural experiment to demonstrate that when measuring investment-cash flow sensitivity, the value of a firm's assets that can be used as collateral should be taken into account. Using panel data on U.S. firms from 1990 to 2011, it was found that the share of physical capital in assets has a strong influence on investment-cash flow sensitivity, which decreased substantially after the crisis when banks changed their expectations about the value of assets on firms' balance sheets. This paper deepens our understanding of firms' investment behavior.